Developing and validating polygenic risk scores for colorectal cancer risk prediction in East Asians. Issue 10 (21st July 2022) - Ping, Jie; Yang, Yaohua; Wen, Wanqing; Kweon, Sun‐Seog; Matsuda, Koichi; Jia, Wei‐Hua; Shin, Aesun; Gao, Yu‐Tang; Matsuo, Keitaro; Kim, Jeongseon; Kim, Dong‐Hyun; Jee, Sun Ha; et al.
Abstract: Several polygenic risk scores (PRSs) have been developed to predict the risk of colorectal cancer (CRC) in European descendants. We used genome‐wide association study (GWAS) data from 22 702 cases and 212 486 controls of Asian ancestry to develop PRSs and validated them in two case‐control studies (1454 Korean and 1736 Chinese). Eleven PRSs were derived using three approaches: GWAS‐identified CRC risk SNPs, CRC risk variants identified through fine‐mapping of known risk loci and genome‐wide risk prediction algorithms. Logistic regression was used to estimate odds ratios (ORs) and area under the curve (AUC). PRS115‐EAS, a PRS with 115 GWAS‐reported risk variants derived from East‐Asian data, validated significantly better than PRS115‐EUR derived from European descendants. In the Korea validation set, OR per SD increase of PRS115‐EAS was 1.63 (95% CI = 1.46‐1.82; AUC = 0.63), compared with OR of 1.44 (95% CI = 1.29‐1.60, AUC = 0.60) for PRS115‐EUR . PRS115‐EAS/EUR derived using meta‐analysis results of both populations slightly improved the AUC to 0.64. Similar but weaker associations were found in the China validation set. Individuals among the highest 5% of PRS115‐EAS/EUR have a 2.52‐fold elevated CRC risk compared with the medium (41‐60th) risk group and have a 12% to 20% risk of developing CRC by age 85. PRSs constructed using results from fine‐mapping and genome‐wide algorithms did not perform as well as PRS115‐EAS and PRS115‐EAS/EUR in risk prediction, possibly due to a small sample size. Our results indicate that CRC PRSs are promising in predicting CRC risk in East Asians and highlights the importance of using population‐specific data to build CRC risk prediction models. What's new?: Several polygenic risk scores (PRS) have been developed to predict colorectal cancer risk in European‐ancestry populations. Using data from large genome‐wide association studies, here the authors developed and validated PRSs for colorectal cancer risk prediction in East Asians. The PRS derived from this study showed a similar discriminatory ability in classifying cases and controls as that previously reported in European‐ancestry populations. The findings support the utility of PRSs in identifying high‐risk individuals for colorectal cancer prevention in Asians and highlight the importance of using population‐specific data to build colorectal cancer risk prediction models.